Biochemical study on the effect of Toxoplasma gondii on Liver function in Women - Muhsin, Salwa Suber; Jafar, Eman Hussain; Jafar, Nasser Sadaq (The Iraqi Journal of Veterinary Medicine, 2013)
The aim of this study was to detect the effect of toxoplasmosis on some liver enzyme activity such as bilirubin concentration, Alanine aminotransferase (ALT), Aspartate aminotransferase (AST), Alkaline Phosphatase (ALP) in serum. Twenty hundred and fifty women were examining by Enzyme-linked immunosorbent assay (ELISA). One hundred and thirty-four were infected with toxoplasmosis with different number of abortion (1-4) times were used in this work. All Serum ALT and AST activities were increased and ALP and total bilirubin level decreased in infected women below the normal value. The analysis of the plasma enzyme distribution pattern suggests that liver cell damage occurred during virulent and low virulent infection, leads to be inflated cells as provided and expansion in Central necrosis of hepatic veins and damage in various parts of the liver